2006
DOI: 10.1002/arch.20142
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression of the Hex 110 gene encoding a glutamine‐rich hexamerin in the honey bee, Apis mellifera

Abstract: An N-terminal amino acid sequence of a previously reported honey bee hexamerin, HEX 110 [Danty et al., Insect Biochem Mol Biol 28:387-397 (1998)], was used as reference to identify the predicted genomic sequence in a public GenBank database. In silico analysis revealed an ORF of 3,033 nucleotides that encompasses eight exons. The conceptual translation product is a glutamine-rich polypeptide with a predicted molecular mass of 112.2 kDa and pI of 6.43, which contains the conserved M and C hemocyanin domains. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 46 publications
7
51
0
11
Order By: Relevance
“…And, some members of Iflavirus are known to be harmful to their hosts by lead to developmental problems and host mortality (van Oers, 2010). For example, sacbrood virus (SBV) is mainly found in larval fat body cells of the honeybee, which may impact metabolic function of these cells, resulting in failure to pupate and ultimately causing death (Bitondi et al, 2006;Park et al, 2016). Interestingly, HaIV was also mainly distributed in the fat body both in larvae and adults while with much lower titers in both the ovary and testis, suggesting a similar function with other members of genus Iflavirus.…”
Section: Discussionmentioning
confidence: 99%
“…And, some members of Iflavirus are known to be harmful to their hosts by lead to developmental problems and host mortality (van Oers, 2010). For example, sacbrood virus (SBV) is mainly found in larval fat body cells of the honeybee, which may impact metabolic function of these cells, resulting in failure to pupate and ultimately causing death (Bitondi et al, 2006;Park et al, 2016). Interestingly, HaIV was also mainly distributed in the fat body both in larvae and adults while with much lower titers in both the ovary and testis, suggesting a similar function with other members of genus Iflavirus.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this is the first systematic study comparing different candidate reference genes for qRT-PCR in honey bees. In previous qRT-PCR studies on this species, reference genes have been selected based on consensus and experience in other organisms, such as ribosomal protein S5-rpS5 (Evans, 2004;Zou et al, 2006), ef1-alpha (Yamazaki et al, 2006), rp49 (Grozinger et al, 2003;Corona et al, 2007), and actin (Lourenço et al, 2005;Bitondi et al, 2006). In a systematic approach to find the best-suited reference genes for qRT-PCR in honey bees, we analyzed the behavior of four candidate reference genes (act, rp49, ef1-alpha and tbp-af) by statistical analyses of variation in different biological conditions and entered these data into three established software programs for reference gene selection, geNorm, BestKeeper and NormFinder.…”
Section: Discussionmentioning
confidence: 99%
“…Hexamerins 70b and 70c exhibit a similar developmental profile because they disappear from the hemolymph with worker emergence, while hexamerin 110 disappears earlier than 70b and 70c (Danty et al 1998). Bitondi et al (2006) found that hexamerin 110 subunits are highly abundant in larval hemolymph, but are decreased at the larval spinning stage, and remain at low levels in pupae and adults (Bitondi et al 2006).…”
Section: Hexamerin-storage or Transport Protein?mentioning
confidence: 99%